2013
DOI: 10.4012/dmj.2012-087
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of H2O2 hydrothermal treatment of aged titanium surface to enhance biofunctional activity

Abstract: Surface modification of titanium has been extensively investigated in implant science and technology in an effort to improve its osteoconductivity. The rate of protein adsorption on titanium surfaces is known to vary depending on the chemistry, structure, morphology, and titanium-specific biological aging of the surface. It is thus desirable to modify smooth titanium surfaces of miniimplants used as orthodontic anchors immediately prior to use. In this study, we have developed a simple surface modification of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…The implant surface treatment technology can increase the total surface area of the implant and enhance bone formation around the implant [12][13][14] . In recent years, surface modification techniques have been applied to the mini-implants to improve the initial stability 15) . Kim et al 16) observed the stability of a surface modified implant (1.8 mm in diameter) that was closer to the root and considered that the proximity of the implant to the tooth root only does not necessarily lead to mini-implant loss, and the underlying cause for implant loosening when close to the root remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The implant surface treatment technology can increase the total surface area of the implant and enhance bone formation around the implant [12][13][14] . In recent years, surface modification techniques have been applied to the mini-implants to improve the initial stability 15) . Kim et al 16) observed the stability of a surface modified implant (1.8 mm in diameter) that was closer to the root and considered that the proximity of the implant to the tooth root only does not necessarily lead to mini-implant loss, and the underlying cause for implant loosening when close to the root remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, we have developed and reported an original technique in which aged Ti-6Al-4V disks were immersed in 3% H 2 O 2 and treated with hydrothermal oxidation at 121 • C /0.2 MPa for 20 min using an autoclave to form a new titanium oxide layer with an about 90 nm thickness, changing the titanium surface to hydrophilic [11]. Using this method, a hydrophilic titanium surface was acquired and protein adsorption and cell adhesion increased.…”
Section: Introductionmentioning
confidence: 99%
“…Acid etching and their combination with heat treatments (thermochemical treatments) are used for the surface modification of titanium, because they modify its elemental and phase composition, but also the topography and wettability. [29][30][31] In addition, this treatment improves the in vitro and in vivo behavior of titanium and its alloys. 9,29,32 Within the chemical procedures used to activate the surface of titanium and its alloys are treatments that enhance the formation of oxides or hydroxides, 30,31,33 and others which enable the formation of titanates (treatments in sodium hydroxide or calcium-ion solutions).…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31] In addition, this treatment improves the in vitro and in vivo behavior of titanium and its alloys. 9,29,32 Within the chemical procedures used to activate the surface of titanium and its alloys are treatments that enhance the formation of oxides or hydroxides, 30,31,33 and others which enable the formation of titanates (treatments in sodium hydroxide or calcium-ion solutions). 16,[34][35][36] The aim of this study is to determine the effect of four treatments of surface activation applied to the commercially pure titanium on the deposition of apatite coatings in a supersaturated calcification solution.…”
Section: Introductionmentioning
confidence: 99%